PENGARUH PENGETAHUAN ANGGOTA DEWAN TENTANG ANGGARAN TERHADAP PENGAWASAN KEUANGAN DAERAH DENGAN TRANSPARANSI KEBIJAKAN PUBLIK DAN AKUNTABILITAS SEBAGAI VARIABEL MODERATING: (STUDI KASUS PADA DPRK KABUPATEN ACEH UTARA) - Dy Ilham Satria; Debi Narisa (Department of Accounting, Faculty of Economics & Business, 2017)
This study aimed to determine the effect of the knowledge of board member about the budget on the supervision of regional finances with the transparency of public policy and accountability as moderating variables. The samples of this study were taken using Census sampling technique in which the entire population used as the sample. Questionnaires were distributed as many as 45 questionnaires and returned 39 questions, then analyzed using Moderated Regression Analysis and the hypothesis were tested using SPSS. The results of this study showed that the knowledge of board members about the budget had a significant positive effect on the supervision of regional finances. The knowledge of board member of budgets with the transparency of public policy as moderating variable influence negatively on the supervision of regional finance. The results of this test indicate that the Transparency of Public Policy weakened the relationship between the knowledge of board members about budgets to the supervision of regional finances. The knowledge of board members about budgets with accountability as a moderating influenced the supervision of regional finances, the results of these tests explained that accountability strengthened the relationship of knowledge of board members on budgets toward the supervision of regional finance. Simultaneous test (f-test) indicated that the knowledge of board members about budgets influenced the supervision of regional finance with the transparency of public policy and accountability as moderating variables that can be seen with the value of sig 0,029 that is less than 0,05 so that the hypothesis was accepted.